Detection of Hb H disease genotypes common in Northern Thailand by quantitative real-time polymerase chain reaction and high resolution melting analyses - Seeratanachot T. (2014)
We used quantitative real-time polymerase chain reaction (qPCR) and high resolution melting (HRM) analyses for the detection of the common α-thalassemia (α-thal) genotypes in 40 northern Thai Hb H (β4) patients. The α0-thal [-SEA (Southeast Asian) deletion] was detected by a multiplex gap real-time PCR. To determine the α+-thal, three primer pairs were designed. The A-primer pair was used to amplify the 3' terminal DNA sequences of the HBA2 gene, and the B-primer pair amplified the 5' flanking region of the HBA1 gene. The C-primer pair amplified the 3' terminal DNA sequences of the HBA1 gene and was used as an internal control. The-α4.2 (leftward) and-α 3.7 (rightward) deletions were determined by monitoring the absence of PCR product(s). The Hb H patients who had a negative PCR result for the A-primer pair but positive for the B-and C-primer pairs carried the-α4.2 deletion, while the-α3.7 deletion carriers were negative for the A-and B-primer pairs. In the case of Hb H with Hb Constant Spring (Hb CS, α142, Term→Gln; HBA2: c.427T>C), all primer pairs were positive, HRM analysis of the PCR product of the A-primer pair was introduced to analyze the Hb CS gene. It can distinguish clearly between normal and Hb CS genotypes. The applied methods for the determination of the α0-and α+-thal genotypes revealed the results to be as accurate as conventional gap-PCR and the direct DNA sequencing methods but resulted in a much simpler and faster procedure. © Informa Healthcare USA, Inc.